Inhibition of carbachol-induced inositol phosphate accumulation in the embryonic retina promoted by kainate and veratridine - Sanches,G. (1998)
In the present study, we report that low concentrations of the glutamate ionotropic agonist kainate decreased the turnover of [3H]-phosphoinositides ([3H]-InsPs) induced by muscarinic receptors in the chick embryonic retina. When 100 µM carbachol was used, the estimated IC50 value for kainate was 0.2 µM and the maximal inhibition of ~50% was obtained with 1 µM or higher concentrations of the glutamatergic agonist. Our data also show that veratridine, a neurotoxin that increases the permeability of voltage-sensitive sodium channels, had no effect on [3H]-InsPs levels of the embryonic retina. However, 50 µM veratridine, but not 50 mM KCl, inhibited ~65% of the retinal response to carbachol. While carbachol increased [3H]-InsPs levels from 241.2 ± 38.0 to 2044.5 ± 299.9 cpm/mg protein, retinal response decreased to 861.6 ± 113.9 cpm/mg protein when tissues were incubated with carbachol plus veratridine. These results suggest that the accumulation of phosphoinositides induced by activation of muscarinic receptors can be inhibited by the influx of Na+ ions triggered by activation of kainate receptors or opening of voltage-sensitive sodium channels in the chick embryonic retina.